2014
DOI: 10.3897/zookeys.457.7380
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology of the sea anemone shrimp Periclimenes rathbunae (Caridea, Palaemonidae, Pontoniinae), from the Caribbean coast of Costa Rica

Abstract: Caridean shrimps are a highly diverse group and many species form symbiotic relationships with different marine invertebrates. Periclimenes rathbunae is a brightly colored shrimp that lives predominantly in association with sea anemones. Information about the reproductive ecology of the species is scarce. Therefore, we collected 70 ovigerous females inhabiting the sun sea anemone Stichodactyla helianthus in coral reefs from the southern Caribbean coast of Costa Rica. Females produced on average 289 ± 120 embry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…An increase in embryonic volume during the ontogeny seems to be common in Decapoda Crustacea (Lardies & Wehrtmann 1997;Terossi et al 2010;Antunes et al 2014;Azofeifa-Solano et al 2014) because the crustacean embryos absorb water and consequently increase in water content (presenting an increasing size) (Pandian 1970). Wear (1974) suggested a close relationship between the increase in embryo volume produced by females during the ontogeny and the number of embryonic and larval stages presented by the species.…”
Section: Fecunditymentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in embryonic volume during the ontogeny seems to be common in Decapoda Crustacea (Lardies & Wehrtmann 1997;Terossi et al 2010;Antunes et al 2014;Azofeifa-Solano et al 2014) because the crustacean embryos absorb water and consequently increase in water content (presenting an increasing size) (Pandian 1970). Wear (1974) suggested a close relationship between the increase in embryo volume produced by females during the ontogeny and the number of embryonic and larval stages presented by the species.…”
Section: Fecunditymentioning
confidence: 99%
“…Periclimenes Costa, 1844 is distributed in the Western Atlantic (Bruce 2004) and comprises species with diverse types of symbiotic relationships (Williams Jr. & Williams 1982;Martinelli-Filho et al 2008;Azofeifa-Solano et al 2014), and Periclimenes paivai Chace 1969 is the only shrimp species reported to associate with the scyphozoan medusoid phase off the Brazilian coast (Criales 1980;Martinelli-Filho et al 2008;Gonçalves, Wolf, et al 2016). However, only the first zoeal stage of P. paivai has been described (Pantaleão et al 2013), and our knowledge about its population biology is scarce.…”
Section: Symbiotic Lifestylementioning
confidence: 99%
“…The mean embryos volume was similar to that in a population of P. northropi studied by Corey & Reid (1991) [44] and to other species of Palaemon, such as P. gravieri [12] and P. longirostris [2] ( Table 1). On the other hand, the embryo volume was higher compared to other Paleomonidae shrimp, such as Cuapetes americanus (Kingsley, 1878) [62] and shrimp of the genus Periclimenes (Costa, 1844) [44,49,57,63]. Differences in embryo volume may be related to differences in the environmental conditions, particularly salinity, of the species' habitats [64].…”
Section: Discussionmentioning
confidence: 97%
“…Caridean shrimps and other decapods adopt a specific behavior during the incubation period, in which females spend some time brushing the embryo mass to remove parasites and to ensure good oxygen supply [56]. This activity is a possible explanation for the low embryo loss in caridean shrimp, such as Periclimenes rathbunae (Schmitt, 1942) [57] and M. acanthurus [7], among others. In this study, the mean embryo volume of P. northropi increased as embryo development proceeded from Stage I to Stage III.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation